(untitled) (Bangladesh Journal of Anatomy, 2017)
Context: The anatomy and shape of a person’s medial longitudinal arch can dictate the types of injuries to which that person is susceptible. Many studies were carried out in various populations to determine normal values of different radiographic dimensions of medial longitudinal arch. However, there is no published article on this topic in Bangladesh. So, this study was aimed to establish the standard data of different medial longitudinal arch radiographic dimensions in adult Bangladeshi male and to make comparison with previous studies on other populations. Materials & Methods: Digital radiographs of left foot in lateral view in bilateral standing position were taken from 50 male students of Sir Salimullah Medical College, Dhaka aged between 21 to 26 years without any history of foot deformities and injuries. These radiographs of foot were imaged with a digital camera according to scale and were transferred to a computer. From these images navicular height, calcaneal inclination angle, medial arch angle and calcaneal-first metatarsal angle were measured by MB ruler software. Results:The mean±SD of the navicular height was 4.90±0.72 cm (range 3.23–6.98 cm), calcaneal inclination angle was 30.82±5.99° (range 15.82°–42.17°), medial arch angle was 109.96±9.09° (range 91.15°–129.42°) and calcaneal-first metatarsal angle was 118.89±10.91° (range 98.53°–148.33°). Bangladesh Journal of Anatomy July 2017, Vol. 15, No. 1, pp. 25-28